2019
DOI: 10.3934/dcdsb.2018315
|View full text |Cite
|
Sign up to set email alerts
|

Uniqueness and traveling waves in a cell motility model

Abstract: We study a non-linear and non-local evolution equation for curves obtained as the sharp interface limit of a phase-field model for crawling motion of eukaryotic cells on a substrate. We establish uniqueness of solutions to the sharp interface limit equation in the so-called subcritical parameter regime. The proof relies on a Grönwall estimate for a specially chosen weighted L 2 norm.Next, as persistent motion of crawling cells is of central interest to biologists we study the existence of traveling wave soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 38 publications
(75 reference statements)
1
8
0
Order By: Relevance
“…However, there is an important difference: tumor growth naturally involves expanding domain while we consider here incompressible solutions. In the context of the motility of eukaryotic cells on substrates, various free boundary problems have been derived and studied, see [2,3,1,15,4,16]. The models presented in [2,3,1,15,16] present some similarities with our model, but they are obtained as the limit of a second order equation of Allen-Cahn type while we obtain ours as the limit of a fourth order equation of Cahn-Hilliard type.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…However, there is an important difference: tumor growth naturally involves expanding domain while we consider here incompressible solutions. In the context of the motility of eukaryotic cells on substrates, various free boundary problems have been derived and studied, see [2,3,1,15,4,16]. The models presented in [2,3,1,15,16] present some similarities with our model, but they are obtained as the limit of a second order equation of Allen-Cahn type while we obtain ours as the limit of a fourth order equation of Cahn-Hilliard type.…”
Section: Introductionmentioning
confidence: 64%
“…In the context of the motility of eukaryotic cells on substrates, various free boundary problems have been derived and studied, see [2,3,1,15,4,16]. The models presented in [2,3,1,15,16] present some similarities with our model, but they are obtained as the limit of a second order equation of Allen-Cahn type while we obtain ours as the limit of a fourth order equation of Cahn-Hilliard type. The model recently proposed in [4] involves a coupled Hele-Shaw/ Keller-Segel type free boundary problem.…”
Section: Introductionmentioning
confidence: 64%
“…In particular, in recent years both free boundary and phase-field models have been extremely successful in replicating, explaining, and predicting experimental results (see, e.g., [13,14,15,16,17,18,19]), see for review [20]. We highlight that recent mathematical analyses have elucidated biological mechanisms [21,22,23,24], and numerical simulations have described a wide range of behaviors ranging from motility initiation via stochastic fluctuations [25] to capturing various modes of motility such as stick-slip and bipedal motions [26,27,28].…”
Section: Introductionmentioning
confidence: 97%
“…We highlight here that the reduction described above is similar to the one conducted in [28] however we additionally incorporate expansions for the V y component. Moreover the equation for the effective adhesion A 0 is derived using the asymptotic expansion A = A 0 (t)ρ(x, y, t)+δA 1 (x, y, t) which gives rise to the effective coefficients (23).…”
mentioning
confidence: 99%
“…In this work we investigate the minimal phase-field model introduced in [6]. Rigorous analysis of its sharp interface limit dynamics was completed in [15,16], where it was observed that persistent cell motion was not stable. In this work we numerically study the pre-limiting phase-field model near the sharp interface limit, to better understand this lack of persistent motion.…”
mentioning
confidence: 99%